2019
DOI: 10.1177/1073110519897736
|View full text |Cite
|
Sign up to set email alerts
|

Country Reports

Abstract: There has been little, if any, discussion of the issue as of now b. There has been discussion among researchers, but little discussion among policy makers c. There has been discussion among both researchers and policy makers d. I am not sure -or other answer 1.1 In Australia, genomic research would require ethics approval like any other human research. DTP research would also attract the general requirements for approving human research, including minimizing risk and ensuring consent (Chapter 2.1-2.3 National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The countries taking this position were Australia, Brazil, Denmark, India, Peru, Qatar, South Africa, Spain, and Switzerland. While Australian researchers are “required to consider” [ 10 ] whether to return research results, for example, Brazil’s Guidelines for Ethical Analysis of Human Genetic Research Projects requires the universal return of individual results unless a participant has explicitly declined to receive them [ 10 ]. In Peru, regulations specify that both individual and aggregate results must be returned.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The countries taking this position were Australia, Brazil, Denmark, India, Peru, Qatar, South Africa, Spain, and Switzerland. While Australian researchers are “required to consider” [ 10 ] whether to return research results, for example, Brazil’s Guidelines for Ethical Analysis of Human Genetic Research Projects requires the universal return of individual results unless a participant has explicitly declined to receive them [ 10 ]. In Peru, regulations specify that both individual and aggregate results must be returned.…”
Section: Resultsmentioning
confidence: 99%
“…In Peru, regulations specify that both individual and aggregate results must be returned. Other provisions underline the importance of community benefit sharing [ 10 ]. Swiss law similarly provides a right “to be informed of results relating [to health]” and specifies that the communication of results must be carried out in a manner appropriate to the circumstance [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…International research projects are typically subject to oversight from multiple IRBs-one at each participating site or country. In a 31-country survey of ethicolegal experts (hereafter: the "Country Reports"), Rothstein et al found that international DTP genomic research predominantly requires ethics reviews in both the researcher's country, as well as in each country where participants are recruited [1,3]. This survey explored requirements applying to international DTP genomic research, including IRB review, informed consent, local collaborators, restrictions on cross-border sample and data transfers, and rules specific to human genetic research.…”
Section: Introductionmentioning
confidence: 99%